2020
DOI: 10.3892/mmr.2020.10910
|View full text |Cite
|
Sign up to set email alerts
|

Circular RNA cSMARCA5 regulates the progression of cervical cancer by acting as a microRNA‑432 sponge

Abstract: circular rnas (circrnas) have been shown to be involved in the development of cancer. The aim of the present study was to investigate the role of circrna SMarca5 (cSMarca5) in human cervical cancer. in the present study, cSMarca5 expression was upregulated in cervical cancer tissues and cell lines. Furthermore, the proliferation rate of cells transduced with viral plasmids expressing small interfering rna targeting cSMarca5 was downregulated. Bioinformatics analysis predicted that microrna (mir)-432 targeted c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 37 publications
0
30
1
Order By: Relevance
“…However, controversial findings have been reported in another study showing that circSMARCA5 was expressed at higher levels in CC tissues, and knockdown of circSMARCA5 suppressed cellular growth and invasion [102]. The oncogenic functions of circSMARCA5 were mediated through a miR-432/EGFR axis [102]. Besides, the expression of circITCH was significantly decreased in CC tissues compared with the adjacent normal tissues [103].…”
Section: Circrnas As Tumor Suppressors In CCmentioning
confidence: 97%
See 2 more Smart Citations
“…However, controversial findings have been reported in another study showing that circSMARCA5 was expressed at higher levels in CC tissues, and knockdown of circSMARCA5 suppressed cellular growth and invasion [102]. The oncogenic functions of circSMARCA5 were mediated through a miR-432/EGFR axis [102]. Besides, the expression of circITCH was significantly decreased in CC tissues compared with the adjacent normal tissues [103].…”
Section: Circrnas As Tumor Suppressors In CCmentioning
confidence: 97%
“…Recent data suggest that circSMARCA5 was downregulated in CC tissues compared with adjacent normal tissues, and overexpression of circSMARCA5 suppresses the proliferation and invasion of HeLa cells by sponging miR-620 [82]. However, controversial findings have been reported in another study showing that circSMARCA5 was expressed at higher levels in CC tissues, and knockdown of circSMARCA5 suppressed cellular growth and invasion [102]. The oncogenic functions of circSMARCA5 were mediated through a miR-432/EGFR axis [102].…”
Section: Circrnas As Tumor Suppressors In CCmentioning
confidence: 99%
See 1 more Smart Citation
“…although the alterations in the KeGG pathway may be caused by high levels of blood-glucose in our model, the results still preliminarily suggested that these circrnas may have an association with early stage dcM and the function of these circrnas needs further investigation. numerous studies have shown that circrnas may negatively regulate the inhibitory effects of mirnas on their target mrnas by directly binding to mirnas, thereby acting as mirna sponges (24,35,40,(45)(46)(47). in the present study, mmu_circ_0000652 and mmu_circ_0001058 were found to potentially interact with mir-195 and mir-21, both of which have been shown to serve roles in the metabolism of dcM.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have shown that circRNAs may negatively regulate the inhibitory effects of miRNAs on their target mRNAs by directly binding to miRNAs, thereby acting as miRNA sponges ( 24 , 35 , 40 , 45 47 ). In the present study, mmu_circ_0000652 and mmu_circ_0001058 were found to potentially interact with miR-195 and miR-21, both of which have been shown to serve roles in the metabolism of DCM.…”
Section: Discussionmentioning
confidence: 99%